Investigation of Some Characterizations of Black TiO\(_2\) Nanotubes Via Spectroscopic Methods - Nguyen, Tho Truong; Cao, Thi Minh; Le, Hieu Van; Pham, Viet Van (Communications in Physics, 2019)
The black TiO\(_2\) with substantial Ti\(^3+\) and oxygen vacancies exhibit an excellent photoelectrochemical water-splitting performance due to the improved charge transport the extended visible light response. In this study, black TiO\(_2\) nanotube arrays synthesized by the anodization method, and then, they have been investigated some characterizations by spectroscopic methods such as UV-visible reflectance (UV-vis DRS), Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, and photoluminescence spectrum. The results showed that some highlighted properties of the black TiO2 nanotube arrays and they could apply for water-splitting effect